Features of Structural and Functional Changes in the Heart in Elderly Patients with Coronary Heart Disease and Atrial Fibrillation - L. I. Folomeeva; E. V. Filippov (Рациональная фармакотерапия в кардиологии)
Supraventricular arrhythmias, including atrial fibrillation (AF), are a current problem for patients in the older age group due to the possibility of lifethreatening complications. Elderly patients have pre-conditions for the development of supraventricular rhythm disturbances (age-related structural and functional changes in the myocardium, concomitant diseases).Aim. To study the features of structural and functional changes in the myocardium of the left heart in elderly patients, depending on the presence of supraventricular arrhythmias.Material and methods. The cross-sectional study included 200 individuals aged 60 to 89 years. All participants underwent echocardiographic examination and 24-hour electrocardiogram (ECG) monitoring. The patients of the study cohort were divided into 3 groups: group 1 consisted of patients with coronary heart disease (CHD) without heart rhythm disturbances (n=80); group 2 consisted of patients with CHD and paroxysmal AF (n=40); group 3 consisted of patients with CHD and supraventricular extrasystoles (n=40). The control group consisted of patients of the older age group without CHD and rhythm disturbances (n=40).Results. In patients with paroxysmal AF and frequent supraventricular extrasystoles, large sizes of the left atrium were revealed (anteroposterior dimension: 4.30±0.07 and 4.12±0.12 cm; upper-lower: 6.15±0.03 and 5.96±0.10 cm; medial-lateral: 4.15±0.11 and 3.87±0.09 cm, respectively). In patients with CHD and rhythm disturbances, the presence of a combined increase in the size of the left atrium and a decrease in myocardial contractility was revealed (ejection fraction of the left atrium in groups 2 and 3 – 27.2±0.1% and 27.9±0.1%, respectively, vs 36.3±0.1% and 38.20±0.02%, respectively in group 1 and control). The duration of ischemic changes during 24-hour ECG monitoring was also greater in group 3 compared with groups 1 and 2 (249.6 vs 27.1 and 66.4 min, respectively). In groups 2 and 3, a discordant effect of the sympathetic and parasympathetic nervous systems on heart rate variability was revealed.Conclusion. For elderly patients, morphological and functional changes are characteristic, which consist in the restructuring of the myocardium and changes in heart rate variability with a prevalence of the sympathetic part of the autonomic nervous system.